Thermal Stability and the Effect of Water on Hydrogen Fluoride Generation in Lithium-Ion Battery Electrolytes Containing LiPF6 - Han, Ji Yun; Jung, Seungho (Batteries, 2022)
Lithium-ion batteries (LIBs) have been used as electrochemical energy storage devices in various fields, ranging from mobile phones to electric vehicles. LIBs are composed of a positive electrode, a negative electrode, an electrolyte, and a binder. Among them, electrolytes consist of organic solvents and lithium ion conducting salts. The electrolytes used in LIBs are mostly linear and cyclic alkyl carbonates. These electrolytes are usually based on their combinations to allow the use of Li as the anodic active component, resulting in the high power and energy density of batteries. However, these organic electrolytes have high volatility and flammability that pose a serious safety issue when exposed to extreme conditions such as elevated temperatures. At that time, these electrolytes can react with active electrode materials and release a considerable amount of heat and gas. In this study, a simultaneous thermal analysis-mass spectrometry analysis was performed on six different organic solvents to examine the effect of water on hydrogen fluoride (HF) generation temperature in the electrolyte of a LIB. The electrolytes used in the experiment were anhydrous diethyl carbonate, 1,2-dimethoxyethane, ethylene carbonate, 1,3-dioxolane, tetrahydrofurfuryl alcohol, and 2-methyl-tetrahydrofuran, each containing LiPF6. The HF formation temperature was observed and compared with that when water entered the electrolyte exposed to high-temperature conditions such as fire.
Keywords: Battery electrolyte; Effect of water; Electrochemical energy storage devices; Exposed to; Generation temperature; Hydrogen fluoride; Hydrogen fluoride generation temperature; LiPF6 salt; Lithium-ion battery electrolyte; TG/DTA-MS analyse; HF generation temperature; LiPF6 salt; lithium-ion battery electrolytes; TG/DTA-MS analysis; thermal stability